2018
DOI: 10.1111/tct.12778
|View full text |Cite
|
Sign up to set email alerts
|

Blended learning to teach gender in medical school

Abstract: Using blended learning techniques, a flipped classroom workshop on gender and sexuality was developed in 2016. The workshop had online components that gave basic information on gender and sexuality, which students viewed prior to the face-to-face session. Students then discussed specific gender-related topics with expert facilitators using a timed multi-station approach during the face-to-face session. A plenary session provided students with the opportunity to address any remaining questions. Evaluation sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 9 publications
0
18
0
6
Order By: Relevance
“…McGarry et al (2002) noted improvements in medical residents' self-reported level of preparation and comfort in LGBT health after the training. Similarly, Michael and Marjadi (2018) found that medical students' increased their self-reported knowledge on gender and sexual health services for LGBTQ patients. Finally, Sequeira et al (2012) reported that 82% of pre-clinical medical students could articulate how to inquire about the gender of a patient's sexual partner among LGBT patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…McGarry et al (2002) noted improvements in medical residents' self-reported level of preparation and comfort in LGBT health after the training. Similarly, Michael and Marjadi (2018) found that medical students' increased their self-reported knowledge on gender and sexual health services for LGBTQ patients. Finally, Sequeira et al (2012) reported that 82% of pre-clinical medical students could articulate how to inquire about the gender of a patient's sexual partner among LGBT patients.…”
Section: Discussionmentioning
confidence: 92%
“…LGBT] youth; knowledge and skills of LGBT issues; sexual orientation) and all 11 of these studies reported a statistically significant improvement after the training (Bakhai et al, 2016;Bristol et al, 2018;Carabez et al, 2015b;Dielissen et al, 2014;Eriksson and Safer, 2016;Kelley et al, 2008;Porter and Krinsky, 2014;Strong and Folse, 2015;Vance et al, 2017Vance et al, , 2018Vogt et al, 2008). Six studies reported improvements in gender-related health knowledge but did not test for statistical significance (Bockers et al, 2017;Braun et al, 2017;Dielissen et al, 2009;McGarry et al, 2002;Michael and Marjadi, 2018;Sequeira et al, 2012). For example, Bockers et al (2017) found the majority of participants learned to recognise gender stereotypes in the medical profession.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the April 2018 issue of The Clinical Teacher we published an article from the UK about a teaching session for second‐year medical students that focused on LGBT health care . In this issue we have one paper from Australia on teaching about gender and sexuality, and two papers from the USA about transgender health in adolescents and children …”
mentioning
confidence: 99%
“…Yet LGBTIQ people are at risk of encountering homophobia and heterosexism, which the article defines as an ‘ideology that denies, denigrates and stigmatises any non‐heterosexual form of behaviour, identity or relationship’, drawing on the work of Herek . At Western Sydney University gender and sexuality education are embedded throughout the medical programme, with early learning via a flipped classroom model …”
mentioning
confidence: 99%